Golan Heights and its Impacts on Iran and US Foreign Policy - Shahzad Khan (Social Science Review Archives, 2025)
The Golan Heights, a geopolitically crucial plateau located at the intersection of Israel, Syria, Lebanon, and Jordan, continues to be one of the most disputed and powerful regions of Middle Eastern geopolitics. Conquered by Israel in the 1967 Six-Day War and annexed unilaterally in 1981—a step broadly disapproved of by the international community—the area has since figured prominently in the determination of foreign policy by the key regional and global powers, notably Iran and the United States. This analysis examines the tripartite importance of the Golan Heights, analyzing its military, geographic, and symbolic importance. This paper examines Iran's increasing role in the region through its strategic alliance with Syria, its proxy of Hezbollah, and its larger campaign to combat Israeli and Western influence via proxy war and ideological battle. At the same time, the research analyzes the changing attitude of the United States—from classic diplomatic prudence to the Trump government's recognition in 2019 of Israeli sovereignty, and the Biden administration's more circumspect, law-based reaction. The study explores the consequences of the Golan Heights on regional security, cyber and hybrid conflict, and international law. It contends that the territory is a borderland, but a geopolitical lever too—deployed by Tehran and Washington alike to exercise influence, deter rivals, and condition the wider strategic environment in the Levant. Ultimately, the Golan Heights remains a symbol of unfinished conflict and a possible flashpoint that has continued to complicate long-term peace and stability efforts in the Middle East.